Expression of FOXM1 and PLK1 in Colorectal Cancer and Their Relationship with Clinicopathological Features and Prognosis - Xue HAN; Shuqing LIU; Jiangling YIN; Changcheng WANG (Zhongliu Fangzhi Yanjiu)
ObjectiveTo determine the expression of FOXM1 and PLK1 in colorectal cancer tissues and their relationship with clinicopathological characteristics and prognosis of patients. MethodsSixty patients who underwent surgical resection of colorectal cancer were retrospectively selected. Colorectal cancer tissues and adjacent tissues (>5 cm from the margins of colorectal cancer tissues) were collected. Immunohistochemistry, Western blot, and qRT-PCR analyses were used to detect the expression levels of FOXM1 and PLK1 in colorectal cancer tissues. Human colon cancer HCT-116 cells were treated with FOXM1 inhibitor FDI-6, and the effect of downregulating FOXM1 on PLK1 expression levels was investigated by Western blot and qRT-PCR. ResultsFOXM1 and PLK1 were highly expressed in the cytoplasm of colorectal cancer cells, and the positive expression rate was significantly higher than those in adjacent tissues (P<0.05). FOXM1 expression was closely related to the degree of differentiation, TNM stage, lymph node metastasis, and invasion depth (all P<0.05). PLK1 expression was closely related to TNM stage, lymph node metastasis, and invasion depth (all P<0.05). The expression levels of FOXM1 and PLK1 in colorectal cancer tissues were positively correlated (rs=0.373, P=0.003). Western blot and qRT-PCR results showed that the expression level of PLK1 decreased significantly after inhibition of FOXM1 expression. Patients with either FOXM1 or PLK1 expression alone, or with neither expressed, had significantly longer survival time and more favorable prognosis than those with FOXM1 and PLK1 co-expression. ConclusionFOXM1 and PLK1 are highly expressed in colorectal cancer tissues. FOXM1 may promote colorectal cancer through PLK1, and its high expression suggests poor prognosis of patients and may be a potential target for colorectal cancer.